Wireless Textile Moisture Sensor for Wound Care - Tessarolo, Marta; Possanzini, Luca; Gualandi, Isacco; Mariani, Federica; Torchia, Leo Davide; Arcangeli, Danilo; Melandri, Federico; Scavetta, Erika; Fraboni, Beatrice (Frontiers in Physics, 2021)
One of the main problems of hard-to-heal wounds regards the monitoring of their healing progress. Currently, clinicians monitor the wound's status by removing the dressing, disturbing the healing process. A relevant parameter that they need to monitor is wound moisture. Indeed, a low amount of exudate can desiccate the wound, while a high level of moisture will lead to maceration. Thus, to optimize the healing process, it is particularly important to maintain an optimum level of moisture, while limiting unnecessary dressing changes. An innovative solution to address this issue is the design of a bandage with an integrated moisture sensor. In this work, we developed a textile sensor based on a conductive polymer poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) that discriminates wound's moisture level. PEDOT:PSS is screen printed on a gauze in a specific geometry. Exploiting its intrinsic electrochemical properties, the sensor operates in real time by monitoring impedance variations that span over several orders of magnitude between dry and wet states. The sensor is directly integrated with an RFID chip, implementing a real-time wireless monitoring. The final device results in a low-cost, user friendly, disposable and wirelessly connected patch.